Assessment of onshore wind energy potential in Peninsular Malaysia - Shaf'i, Herul Azrul (2015)
Wind power and other sources of renewable energy are gaining attention as an alternative to replace demanding on traditional energy sources that scarce. However, wind energy still need to be developed and probably to commercialized as a huge renewal energy sources. The wind data with duration from year 2010 till 2014 was collected from Malaysian Meteorological Department (MMD) stations across Peninsular Malaysia, namely; Langkawi Island, Malacca, Mersing, Kuantan, Kota Terengganu and Kota Bahru. All selected area and wind data were analysed and simulated using Vector data by Geographic Information System(ArcGIS) and Wind Atlas Analysis and Application Program (WAsP) software. The resulted analysis from collected data shows a rated of wind speed and wind direction. The wind rose chart and Weibull distribution obtained was summarizing a wind power density. The overall results of this study show that the assessment and analysis of wind energy in Malaysia has potential to growth by developing small and medium scale of wind farms in order to generate a power sources which are clean, non-polluting and renewable.